PERAN GURU DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI METODE DISCOVERY LEARNING PADA MATA PELAJARAN IPAS - Luky Arfianti; Zulfatun Anisah; Rinatul Khumaimah (PREMIERE : Journal of Islamic Elementary Education, 2025)
This study investigates the role of teachers in developing students' critical thinking skills in IPAS (Natural and Social Sciences) subject, specifically on animal body parts, for third-grade students at MI Bahrul Ulum through the Discovery Learning method. The background highlights the crucial role of teachers in fostering critical thinking from an early age, especially in the 21st-century learning context. The research aims to explore the teacher's role, the implementation of Discovery Learning, and the challenges faced. Employing a qualitative descriptive approach, data were collected through observation, interviews with the headmaster and third-grade teacher, and documentation. The findings indicate that teachers act as effective facilitators, mentors, and motivators, actively engaging students in exploratory and reflective learning processes. The systematic application of Discovery Learning stages (stimulation, problem statement, data collection, data processing, verification, and generalization) significantly improved students' critical thinking indicators, such as problem identification, observation explanation, and conclusion drawing. Despite challenges like time constraints and varied student readiness, teachers demonstrated adaptive strategies to ensure meaningful learning outcomes.